2008
DOI: 10.1159/000176309
|View full text |Cite
|
Sign up to set email alerts
|

Interest of ImmunoCAP System to Recombinant ω-5 Gliadin for the Diagnosis of Exercise-Induced Wheat Allergy

Abstract: Background: ω-5 gliadin is a major allergen in exercise-induced wheat allergy (EIWA), but it is also implicated in immediate-type reactions to wheat. An ImmunoCAP assay to measure ω-5 gliadin-specific IgE has become available. This study aimed to evaluate this new biological test in wheat allergy diagnosis and to also determine if it was able to discriminate EIWA from other types of wheat allergy. Methods: Sixty-one patients with wheat allergy were divided into 3 groups as a function of their symptoms (EIWA, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 46 publications
0
31
1
2
Order By: Relevance
“…It seems obvious as the ω-5 gliadin fractions act as the main allergens in WDEIA [18,[32][33][34]. However, ω-5 can be also active in other wheat allergies [21,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems obvious as the ω-5 gliadin fractions act as the main allergens in WDEIA [18,[32][33][34]. However, ω-5 can be also active in other wheat allergies [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…One of the important findings in allergology was to prove that ω-5 gliadins are the main allergens involved in wheat-dependent exerciseinduced anaphylaxis (WDEIA) -the most dangerous, life threating form of wheat allergy [16][17][18]. Omega-5 gliadins may also trigger other wheat allergies, described as exerciseinduced wheat allergy (EIWA) [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other gliadin classes, however, especially cgliadins, may also be active in anaphylactic reactions (Palosuo et al 1999;Morita et al 2000) but to a lesser extent. Jacquenet et al (2009) concluded that elimination of x-5 gliadins may completely eliminate the risk associated with consumption of foodstuffs made from wheat flour.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, immunoglobulin E (IgE) specific to wheat or ω-5 gliadin can be measured using the ImmunoCAP system (Phadia, Uppsala, Sweden) [4]. …”
Section: Introductionmentioning
confidence: 99%